2009
DOI: 10.1021/ic901964f
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Making Organometallic Compounds with BF Ligands: Fluoroborylene Iron Carbonyls

Abstract: The fluoroborylene ligand (BF), isoelectronic with CO, was recently (2009) realized experimentally by Vidović and Aldridge in Cp(2)Ru(2)(CO)(4)(mu-BF). In this research the related iron carbonyl fluoroborylene complexes Fe(BF)(CO)(n) (n = 4, 3), Fe(2)(BF)(CO)(8), and Fe(2)(BF)(2)(CO)(n) (n = 7, 6) are compared with the isoelectronic Fe(CO)(n+1) and Fe(2)(CO)(n+2) as well as the thiocarbonyls Fe(CS)(CO)(n) and Fe(2)(CS)(2)(CO)(n) using density functional theory. For Fe(BF)(CO)(4) the axially and equatorially su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…This difference in chemical shift signifies that p-donation from fluorine to boron in 2 is substantially diminished relative to B-O p-bonding in the oxyboryl group and is reflective of the greater electronegativity of the fluorine atom in the BF unit. Complex 2 also gives rise to a 19 F NMR resonance at d F = +1.6 ppm, which is significantly downfield relative to that found in the dinuclear bridging BF complex (m 2 -BF)[CpRu(CO) 2 ] 2 (d F = -185.0 ppm) (20) and BF 3 •Et 2 O (d F = -153 ppm). Rapid quadrupolar relaxation of the I = 3/2 11 B nucleus prevented a determination of the 1 J BF coupling constant in both the one-dimensional (1D) 11 B and 19 F NMR spectra of 2.…”
mentioning
confidence: 89%
“…This difference in chemical shift signifies that p-donation from fluorine to boron in 2 is substantially diminished relative to B-O p-bonding in the oxyboryl group and is reflective of the greater electronegativity of the fluorine atom in the BF unit. Complex 2 also gives rise to a 19 F NMR resonance at d F = +1.6 ppm, which is significantly downfield relative to that found in the dinuclear bridging BF complex (m 2 -BF)[CpRu(CO) 2 ] 2 (d F = -185.0 ppm) (20) and BF 3 •Et 2 O (d F = -153 ppm). Rapid quadrupolar relaxation of the I = 3/2 11 B nucleus prevented a determination of the 1 J BF coupling constant in both the one-dimensional (1D) 11 B and 19 F NMR spectra of 2.…”
mentioning
confidence: 89%
“…Boron monofluoride is also isoelectronic to CO and N 2 , and was predicted to be both a stronger σ-donor and π-acceptor compared against CO. [84][85][86] It possesses a lower bond order and like CO, the dipole moment of BF is in the opposite direction of intuition, with the B atom as the negative pole. 87,88 However, BF is only stable under extreme conditions, rendering its coordination compounds difficult to prepare.…”
Section: Binding Of Co With Beo and Becomentioning
confidence: 99%
“…However, the trigonal bipyramidal geometry in (BF)Fe(CO) 2 (CNAr Tripp2 ) 2 has an obvious distortion and the C1-FeÀ C2 bond angle is only 157.5°, which may come from the better σ-acceptor properties of BF. [18,20] The trigonal bipyramidal geometry in [(CN)Fe(CO) 2 (CNAr Tripp2 ) 2 ] À has been obviously distorted, in which the bond angle of C1À FeÀ C2 in is 144.3°while the C N (equatorial) À FeÀ C O (equatorial) is as large as 167.6°. Besides, the E 1 À E 2 bond in (E 1 E 2 )Fe (CO) 2 (CNAr Tripp2 ) 2 is elongated moderately by about 0.02 Å with respect to the free E 1 E 2 except for the distorted [(NO)Fe (CO) 2 (CNAr Tripp2 ) 2 ] + .…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Fluoroborylene iron carbonyls and homoleptic fluoroborylenes complexes have also been proposed theoretically by Hoffmann and Schaefer and King. [18][19][20][21][22][23][24] Very recently, Figueroa et al successfully realized the isolation of the iron complex (BF)Fe(CO) 2 (CNAr Tripp2 ) 2 [Ar Tripp2 = 2,6-(2,4,6-(iso-propyl) 3 C 6 H 2 ) 2 C 6 H 3 ] with a terminal BF ligand, along with the isoelectronic dinitrogen and CO complexes (N 2 ) Fe(CO) 2 (CNAr Tripp2 ) 2 and Fe(CO) 3 (CNAr Tripp2 ) 2 . [25] Further singlecrystal x-ray diffraction, spectroscopic, and electron-density topology calculation studies demonstrated that the terminal BF ligand possesses particularly strong σ-donor and π-acceptor properties.…”
Section: Introductionmentioning
confidence: 99%